Cardiac L-type calcium channel regulation by Leucine-Rich Repeat-Containing Protein 10 - Natthaphat Siri-Angkul; Timothy J Kamp (Taylor & Francis Group, 2024)
ABSTRACTL-type calcium channels (LTCCs), the major portal for Ca2+ entry into cardiomyocytes, are essential for excitation-contraction coupling and thus play a central role in regulating overall cardiac function. LTCC function is finely tuned by multiple signaling pathways and accessory proteins. Leucine-rich repeat-containing protein 10 (LRRC10) is a little studied cardiomyocyte-specific protein recently identified as a modulator of LTCCs. LRRC10 exerts a remarkable effect on LTCC function, more than doubling L-type Ca2+ current (ICa,L) amplitude in a heterologous expression system by altering the gating of the channels without changing their surface membrane expression. Genetic ablation of LRRC10 expression in mouse and zebrafish hearts leads to a significant reduction in ICa,L density and a slowly progressive dilated cardiomyopathy in mice. Rare sequence variants of LRRC10 have been identified in dilated cardiomyopathy and sudden unexplained nocturnal cardiac death syndrome, but these variants have not been clearly linked to disease. Nevertheless, the DCM-associated variant, I195T, converted LRRC10 from a ICa,L potentiator to a ICa,L suppressor, thus illustrating the wide dynamic range of LRRC10-mediated ICa,L regulation. This review focuses on the contemporary knowledge of LTCC modulation by LRRC10 and discusses potential directions for future investigations.